Salidroside affects the Th17/Treg cell balance in aplastic anemia via the STAT3/HIF-1α/RORγt pathway - Zenghui Liu; Lixuan Chen; Defang Xiong; Yu Zhan; Jiduo Liu; Ling Ouyang; Wancheng Chen; Ziyuan Lu; Tianqi Gao; Xiaozhen Li; Yanqun Zhou; Xuekui Gu; et al. (Redox Report, 2023)
ABSTRACTBackground Acquired aplastic anemia (AA) is a life-threatening disease associated with an imbalance in Th17/Treg cells. Regulating this balance may be an effective treatment approach for AA. Rhodiola rosea has shown efficacy in AA treatment, but its mechanisms remain unclear.Purpose We investigated salidroside's effect (a component of Rhodiola rosea) on Th17/Treg balance in adult AA patients and a mouse model.Methods HIF-1α mRNA and protein levels were measured in AA patients' peripheral blood. Flow cytometry, qRT-PCR, and WB analyzed salidroside's impact on T cell differentiation, Th17 cells, Treg cells, STAT3, HIF-1α, and RORγt expression. ELISA measured hematopoietic growth factors in mouse serum.Results AA patients exhibited elevated HIF-1α levels. Salidroside improved hematopoietic function, increasing blood cell count and enhancing bone marrow. Salidroside induced SCF, TPO, and IL-3 expression while inhibiting IL-2 in mice. Salidroside reduced STAT3, HIF-1α, RORγt, and IL-17a, while increasing FoxP3 expression, correcting the Th17/Treg imbalance in vitro and in vivo.Conclusion Salidroside has potential as a novel AA treatment by correcting the Th17/Treg imbalance through the STAT3/HIF-1α/RORγt pathway.